Bahasa Indonesia Sebagai Media Komunikasi Efektif Dalam Dakwah (Analisis Ustadz Dr. Adi Hidayat, LC., M.A) - Raihan Firdaus Naufal; Muhammad Rizal Khatami (Simpati, 2023)
This article aims to understand the important role of Indonesian in proselytizing or spreading Islam by understanding and mastering Indonesian well. In the context of Indonesian diversity, the use of Indonesian in da'wah needs to pay attention to inclusive and tolerant messages. Language is something that cannot be separated from human life. Preachers can communicate religious messages more effectively to the general public and to avoid the use of inappropriate Indonesian in preaching. The research method used is descriptive qualitative method. Data collection was carried out with data collection techniques through documentation techniques, listening techniques, and recording techniques on da'wah videos delivered by Ustadz Dr. Adi Hidayat, Lc., M.A in the Adi Hidayat Official YouTube Channel. Based on the results of the study, it was found that there was assertiveness in conveying messages and interaction in this case it was also found that Indonesian language in da'wah was better understood, touched the heart, closer between the preacher and the audience so that the audience's interest in the preacher was formed in listening to the da'wah.